PEMBELAJARAN BERDIFERENSIASI MELALUI MEDIA GAMBAR UNTUK MENINGKATKAN KETERAMPILAN MENULIS CERITA FANTASI SISWA KELAS VII - Sahutni, Reza Utami; Syahrani, Agus; Beny, Beny; Khairullah, Khairullah (Jurnal Kajian Pembelajaran dan Keilmuan, 2025)
The skill of writing fantasy stories is the object of research because it leads students to develop creativity and imagination so as to stimulate the brain to think sharper and actively during the intellectual development period of the concrete operational stage. Based on the value of writing fantasy stories done, there are still many students who score below KKM. Students' difficulties in writing fantasy stories include difficulty finding and developing story content, the use of punctuation and vocabulary selection that is still limited, and the use of non-existent approaches and learning media that make students less motivated to write fantasy stories. The research method used is a descriptive method with the form of CAR and includes qualitative research. The source of data in the study was 33 students in grade VII F and the data obtained was the result of students' skills in writing fantasy stories. Student learning outcomes have improved fantasy story writing skills by applying differentiated learning through image media. Students in cycle I obtained an average score of 13.90 or 69.50% with category B (Good) and in cycle II increased with an average score of 15 or 75% with category SB (Very Good). In cycle I there were 23 students who were complete and 10 students who were incomplete and in cycle II there were 26 students who were complete and 7 students who were incomplete.